Analysis of Nursing Care in Hypertensive Patients with Acute Pain Nursing Problems Given in Combination with Hand Massage with Lavender Aromatherapy at Anugerah Denpasar Clinic - Dewi, Ni Luh Wiwin Yulistina; Sari, Ni Luh Putu Dian Yunita; Prihandani, I GAA Sherlyna (PROMOTOR, 2025)
Hypertension is a non-communicable disease (NCD) that can cause pain in the neck to the head. Pain can be overcome through the provision of aromatherapy and massage or even a combination of both, for example hand massage using essential oils, one of which is lavender. This study aimed to analyze nursing care in hypertensive patients with acute pain nursing problems given a combination of hand massage with lavender aromatherapy at Anugerah Denpasar Clinic. The method used was a case study on 3 patients with hypertension. The given was doing a hand massage using lavender essential oil for 10 minutes in 3 days. The results of the study on 3 hypertensive patients showed that hand massage using lavender aromatherapy was effective in overcoming acute pain problems in patients by achieving the outcome criteria, namely decreased pain perception/feeling, decreased pain scale, vital signs in the normal range and patients appeared calm, did not endure pain or grimacing. Hand massage with lavender aromatherapy can be used as an alternative non-pharmacological treatment to overcome pain problems in patients.